Regional Economic Outlook, October 2020, Middle East and Central Asia. (International Monetary Fund, 2020)
Countries in the Middle East, North Africa, Afghanistan, and Pakistan (MENAP) region and those in the Caucasus and Central Asia (CCA) responded to the COVID-19 pandemic with swift and stringent measures to mitigate its spread and impact but continue to face an uncertain and difficult environment. Oil exporters were particularly hard hit by a 'double-whammy' of the economic impact of lockdowns and the resulting sharp decline in oil demand and prices. Containing the health crisis, cushioning income losses, and expanding social spending remain immediate priorities. However, governments must also begin to lay the groundwork for recovery and rebuilding stronger, including by addressing legacies from the crisis and strengthening inclusion.